CHES: A Space-borne Astrometric Mission for the Detection of Habitable Planets of the Nearby Solar-type Stars. (1st July 2022) - Ji, Jiang-Hui; Li, Hai-Tao; Zhang, Jun-Bo; Fang, Liang; Li, Dong; Wang, Su; Cao, Yang; Deng, Lei; Li, Bao-Quan; Xian, Hao; Gao, Xiao-Dong; Zhang, Ang; et al.
Abstract: The Closeby Habitable Exoplanet Survey (CHES) mission is proposed to discover habitable-zone Earth-like planets of nearby solar-type stars (∼10 pc away from our solar system) via microarcsecond relative astrometry. The major scientific objectives of CHES are: to search for Earth Twins or terrestrial planets in habitable zones orbiting 100 FGK nearby stars; further to conduct a comprehensive survey and extensively characterize nearby planetary systems. The primary payload is a high-quality, low-distortion, high-stability telescope. The optical subsystem is a coaxial three-mirror anastigmat (TMA) with a 1.2 m-aperture, 0.°44 × 0.°44 field of view and 500 nm−900 nm working wave band. The camera focal plane is composed of a mosaic of 81 scientific CMOS detectors each with 4 k × 4 k pixels. The heterodyne laser interferometric calibration technology is employed to ensure microarcsecond level (1 μ as) relative astrometry precision to meet the requirements for detection of Earth-like planets. The CHES satellite operates at the Sun–Earth L2 point and observes all the target stars for 5 yr. CHES will offer the first direct measurements of true masses and inclinations of Earth Twins and super-Earths orbiting our neighbor stars based on microarcsecond astrometry from space. This will definitely enhance our understanding of the formation of diverse nearby planetary systems and the emergence of other worlds for solar-type stars, and finally provide insights to the evolution of our own solar system.